Collins & Gitelman, Thomas Edison And Modern America - A Brief History With Documents - Dalton, C. David (Teaching History: A Journal of Methods, 2004)
Arguably, no individual personifies the emergence of modem America better than Thomas Edison. He received over 1000 patents between 1869 and 1931, a period marked by tremendous growth in immigration, urbanization, domestic and foreign expansion, and of course industrialization